(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the pioneering work of the scientist and religious figure Herman Gabriel Farhat (1670–1732) in the field of compiling grammatical works called Bakhs al-matalib wa hass al-talib. The purpose of this article is to identify the author’s innovative methods in writing his book, which differ from earlier classical grammatical sources. To solve the problem, general scientific research methods were used within the framework of scientific description, comparative typological, structural-semantic and comparative historical analysis. As a result of the study, the following results were revealed: the author, for the first time in the history of writing essays on Arabic grammar, began his work with an explanation of the alphabet and places of articulation of letters. Moreover, he was one of the first to combine morphology and syntax into one book, while devoting a separate chapter to the morphological analysis of syntactic structures. This, in turn, gives grounds for the conclusion that the author of Bakhs al-matalib wa hass al-talib widely used data from earlier sources, transmitting them in a certain systematic manner and in an accessible form and language, thereby contributing to its popularization both among grammarians and and between researchers.